(untitled) (Academicia Globe: Inderscience Research, 2022)
In this article, a pressupositive study of the stories of Ernest Hemingway and Abdullah Kahhor, trivalent calculations of the presupposition, a specific style in the stories of Ernest Hemingway, three conditional directions of the stories of Abdullah Kahhor, a specific dynamic phenomenon of the presupposition, the image of Ernest Hemingway and Abdullah Kahhor structure, the drama of Hemingway’s prose.